Radio-Protective Effects of Stigmasterol on Wheat (Triticum aestivum L.) Plants - Hebat-Allah A. Hussein; Shifaa O. Alshammari; Fatma M. Elkady; Amany A. Ramadan; Sahar K. M. Kenawy; Aisha M. Abdelkawy (MDPI AG, 2022)
Ionizing radiation is abiotic stress limiting the growth and productivity of crop plants. Stigmasterol has positive effects on the plant growth of many crops. The role of stigmasterol in alleviating the effects of ionizing radiation on plant metabolism and development is still unclear. Therefore, the study aimed to investigate the effects of pretreatments with γ-radiation (0, 25, and 50 Gy), foliar application of stigmasterol (0, 100, and 200 ppm), and their interaction on the growth, and biochemical constituents of wheat (Triticum aestivum L., var. Sids 12) plants. Gamma radiation at 25 Gy showed no significant difference in plant height, root length, no. of leaves, shoot fresh weight, root fresh weight, Chl a, ABA, soluble phenols, and MDA compared to the control values. Gamma rays at 50 Gy inhibited shoot and root lengths, flag leaf area, shoot fresh and dry weights, photosynthetic pigments, total soluble sugars, proline, and peroxidase activity. However, it stimulated total phenols, catalase activity, and lipid peroxidation. On the other hand, stigmasterol at 100 ppm showed no significant effects on some of the physiological attributes compared to control plants. Stigmasterol at 200 ppm improved plant growth parameters, photosynthetic pigments, proline, phenols, antioxidant enzyme, gibberellic acid, and indole acetic acid. Correspondingly, it inhibited total soluble sugars, abscisic acid, and lipid peroxidation. Moreover, the application of stigmasterol caused the appearance of new polypeptides and the reappearance of those missed by gamma radiation. Overall, stigmasterol could alleviate the adverse effects of gamma radiation on wheat plants.